2021
DOI: 10.1186/s40468-021-00143-4
|View full text |Cite
|
Sign up to set email alerts
|

The practice of online assessment in an EFL context amidst COVID-19 pandemic: views from teachers

Abstract: For many years, technology has been applied to improve the quality of language learning and teaching. However, the outbreak of COVID-19 pandemic accelerated the integration of technology in different language learning contexts. The sudden shift to online teaching faced educators with an array of challenges they had not experienced before. In particular, the teachers encountered many barriers with the online assessment of the students. To shed more light on what passed, following a qualitative mode of inquiry, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 27 publications
5
57
0
6
Order By: Relevance
“…Also, her reflective practices for self-care and the reformation of her teaching showed how she performed the dynamic and flexible roles of a language teacher and confirmed her emerging identity. Similar findings surfaced in the studies on EFL teachers" challenges amid the difficult times (e.g., Davies et al, 2020;Ghanbari & Nowroozi, 2021;Farrell, 2021).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Also, her reflective practices for self-care and the reformation of her teaching showed how she performed the dynamic and flexible roles of a language teacher and confirmed her emerging identity. Similar findings surfaced in the studies on EFL teachers" challenges amid the difficult times (e.g., Davies et al, 2020;Ghanbari & Nowroozi, 2021;Farrell, 2021).…”
Section: Discussionsupporting
confidence: 77%
“…Due to the global health crisis, language teachers were initially confronted with significant administrative, technical, pedagogical, and even affective difficulties; however, they often adapted to these new circumstances -becoming more confident and flexible in teaching on online platforms-as they proceeded through their courses (e.g., Farrell, 2021;Ghanbari & Nowroozi, 2021;Sari, 2021). For instance, Farrell"s (2021) study demonstrated how four EFL novice teachers in Costa Rica overcame their emotional challenges through self-reflection and participatory classroom observations.…”
Section: Efl Teachers' Shifting Challenges Into Opportunities Via Sel...mentioning
confidence: 99%
See 2 more Smart Citations
“…The challenge of the efficiency of similar offline tests to measure the students' really performance levels arises amid the conduction of the test remotely and online. That means students take the test without any direct surveillance that may raise the concerns of teachers on their progress (Fitriyah & Jannah, 2021;Ghanbari & Nowroozi, 2021).…”
Section: Introductionmentioning
confidence: 99%